Radical left, trade unionism and collective action in Andalusia (1976-2012) - Roca Martínez, Beltrán (Cuadernos de Relaciones Laborales, 2014)
In Andalusia, as in other parts of Spain, it has been built a political and union space of leftist organisations which opposed the strategy of the Communist Party, especially after the Moncloa Pacts. This article examines the ideas, strategies and evolution of radical trade unionism in Andalusía from 1976 to 2012, using the different theoretical approaches on collective action. In particular it provides a map of those alternative unions influenced by activists, organisations and ideas of the radical left. Firstly, it describes the main anarcho-syndicalist unions. Secondly, it analyses the wide range of Marxist and/or ethno-nationalist trade unions. The history of such organisations is a succession of lost battles, splits, mergers, coordination efforts, struggles and small victories. Andalusian radical unionism has not achieved to develop agglutinating agents, shared identities and organisational structures capable of challenging the hegemony of the two majority unions. Nevertheless, it has reached a meaningful social influence and projection in certain territories and moments. Finally, the article suggests the main eight factors which explain the maintenance of the Andalusian radical trade unionism. In doing so it uses a synthetic approach on social movements which includes political, organisational and cultural factors.
Keywords: trade unionism; radical left; anarcho-syndicalism; collective action; Andalusia